Antioxidant Activity, Chemical and Sensory Characteristics of Fruit Leather From Red Guava and Red Dragon Fruit - Rahmadini Payla Juarsa; Dewi Fortuna Ayu; Evy Rossi (Jurnal Teknologi Hasil Pertanian, 2024)
Fruit leather is a processed product made from dried fruit puree, thin sheet-shaped with a thickness of 2-3 mm, moisture content of 10-15%, and generally had color and distinctive taste from the fruit as the raw material. The research purpose was to study the effect of red guava (Psidium guajava L) and red dragon fruit (Hylocereus polyrhizus) combination on the antioxidant activity, chemical, and sensory characteristics of the fruit leather.  A complete randomized design consisting of five treatments and three tests was carried out in this study, where the treatment was the ratio of red guava and red dragon fruit puree, namely: JN1 (100%: 0%), JN2 (90%: 10%), JN3 (80%: 20%), JN4 (70%: 30%), and JN5(60%: 40%). Analyzed statistically using Anova and Duncan's new multiple range test at 5% were conducted in this research.  The research showed that a combination of red guava and red dragon fruit significantly affected antioxidant activity, moisture and ash content, degree of acidity (pH), and organoleptic test.  The best fruit leather was JN3 (80% red guava fruit: 20% red dragon fruit) with 12.17% water content, 0.49% ash content, 4.40 pH, and 79.84 µg/ml antioxidant activity.  The overall fruit leather was preferred by the panelists with the description of rather red color, rather red guava-red dragon fruit-flavored, red guava-red dragon fruit taste, and rather springy.